Competency Framework for research data services in Norwegian libraries - Kvale, Live; Bochynska, Agata; Sarre, Aili; Stangeland, Elin; Ostrop, Jenny; Hasle Enerstvedt, Kjersti; Bertheussen, Lene; Pharo, Nils; Sundstøl, Shea; Strandskog Arnesen, Sondre (Septentrio Conference Series, 2022)
“Competency framework for research data services in Norwegian academic libraries” was a one-year project run by the Norwegian Node in the Research Data Alliance with funding from the Norwegian National Library. We present the results from this project. A competency framework defines a set of knowledge and skills needed to develop professionally within a given domain (Rivera-Ibarra et al., 2010). By defining the knowledge needs related to data management in libraries, the project helps to make it easier for institutions to identify the need for skills development. Furthermore, a competence framework can function as a basis for designing educational programmes. Extensive work has been done internationally to define and describe the skills needed to deliver good services in research data management. This competence framework was not intended to duplicate previous work, but rather to describe and refer to good international documents and reports in the field. In addition, we have conducted a full-day workshop with 40 participants from relevant institutions in the sector. Input from the workshop has helped to describe the Norwegian context and factors that apply in this country, which are not highlighted in the international work. We envision the library's role in the work with data management as a hub or filter for the requirements and needs of funders, publishers, and researchers, respectively, which are resolved by further connection to other resources, persons and infrastructure while simultaneously recognizing that the library is a driving force for development work in the field. This approach is deliberately library-centric, in that the library and the coordinating role that the academic libraries usually have is put in the centre. At some institutions, this work may be organized differently, but both in Norway and internationally, the most common model for research data management is for the library to be fully or partially responsible for the field (LIBER, 2020; Swiatek et al., 2020). Some of the key challenges we have identified are that in order to provide support one must have a very wide range of skills while recognizing that it is impossible for one person to know everything. We also see that a majority of those who work with research data management in Norwegian academic libraries have data management as one of several responsibilities. This makes it even more relevant to facilitate collaboration and draw on expertise from others in order to provide good services to the researchers at the institution. When we describe the various types of competence needed to work with data management, it is not with the expectation that a single person will know all this. By making visible the wide range of knowledge needed, we want to make it easier to put into words what competence one has, what competence one wants to acquire in one’s own organization, and what needs to be brought in externally. Here there will be differences in the way in which universities and colleges prioritize.